Factors Affecting the Behavior of Doctors and Nurses on the Prevention of COVID-19 at K.R.M.T Wongsonegoro Hospital - Safarina, Danisa Diandra; Suryawati, Chriswardani; Sutiningsih, Dwi (Universitas Negeri Semarang, 2021)
A viral disease called Corona Virus Disease 19 (COVID-19) had been declared as a pandemic by WHO since March 2020 because the rate of spread is very fast, causing death and having an impact on social and economic aspects. The professions most at risk are health workers including doctors and nurses because they are in direct contact with COVID-19 patients. Doctors and nurses at RSUD K.R.M.T Wongsonegoro also have a high risk, ranging from being infected to dying from the COVID-19 virus, therefore they must have good behavior in preventing COVID-19 infection to protect themselves. The purpose of this study was to identify the factors influencing the behavior of doctors and nurses on the behavior of preventing COVID-19 infection. This research is a cross sectional study using questionnaires distributed to 100 doctors and nurses consisting of general practitioners, specialists and nurses at K.R.M.T Wongsonegoro Hospital in February-March 2021. Among 100 participants, 43% had good behavior and 57% had poor behavior. The factors that are significantly related to the behavior of preventing COVID-19 infection on doctors and nurses at RSUD K.R.M.T Wongsonegoro are motivation and attitude, and the most influential factor is attitude. These results indicate that there are factors that must be maintained so that doctors and nurses maintain good behavior in preventing the transmission of COVID-19 disease, thereby helping to reduce the rate of disease transmission between doctors and nurses, further to the community.